Amdahl's Reliability Law: A Simple Quantification of the Weakest-Link Phenomenon. - Parhami, Behrooz (Computer (00189162), 2015)
Amdahl's performance law is a useful conceptual and pedagogical tool for imparting key ideas about performance limits and the importance of balanced system design to students and practitioners in the field. The weakest-link maxim of reliability engineering can be expressed in terms of an identical formula, giving it a quantitative basis and thus making it more convincing. Calling it "Amdahl's reliability law" stresses the fact that it follows directly from Amdahl's speedup formula.